2014
DOI: 10.1063/1.4862153
|View full text |Cite
|
Sign up to set email alerts
|

Competitive autocatalytic reactions in chaotic flows with diffusion: Prediction using finite-time Lyapunov exponents

Abstract: We investigate chaotic advection and diffusion in autocatalytic reactions for time-periodic sine flow computationally using a mapping method with operator splitting. We specifically consider three different autocatalytic reaction schemes: a single autocatalytic reaction, competitive autocatalytic reactions, which can provide insight into problems of chiral symmetry breaking and homochirality, and competitive autocatalytic reactions with recycling. In competitive autocatalytic reactions, species B and C both un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…The correlation changes with advection speed. For small values of Re, reacted regions lie primarily along vortex edges and in narrow filaments where stretching is strongest, consistent with simulations showing that stretching enhances reaction [1,37,38] [31].…”
supporting
confidence: 86%
See 2 more Smart Citations
“…The correlation changes with advection speed. For small values of Re, reacted regions lie primarily along vortex edges and in narrow filaments where stretching is strongest, consistent with simulations showing that stretching enhances reaction [1,37,38] [31].…”
supporting
confidence: 86%
“…When two competing autocatalytic species were simulated in double-gyre flow, it was observed that the one initiated in a region of stronger stretching almost always dominated long term [38]. Similarly, in simulations of competing species in sine flow, another two-dimensional prescribed model, it was observed that local FTLEs accurately predict long-term concentrations [1]. Experiments have shown that the global averaged FTLE is correlated with global reaction rate [39].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…43 Similarly, if two reactions compete, the one that is triggered where FTLEs are smaller is eventually overwhelmed. 2,44 Earlier experiments showed that the overall reaction rate increased when the average FTLE value increased. 45 However, recent evidence 1 suggests that strong stretching may inhibit the growth of reacted regions.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Even without advection, reaction and diffusion give rise to nonlinear phenomena like traveling waves and spiral waves, [14][15][16] so including advection, which may be chaotic or turbulent itself, makes forecasting ARD systems a challenging task. But being able to forecast the spreading of the reacted region (where the concentration of the product species is high) and knowing how its edges will be constrained would allow better prediction of the concentration and uniformity of products in chemical reactors 2,17 and microfluidic devices, 18 more effective safety responses to forest fires, 19,20 and better phytoplankton models for understanding Earth's carbon budget. 12,21,22 In this paper, we present experimental measurements of an ARD system in the wake of a bluff body in a laminar channel flow.…”
mentioning
confidence: 99%